Reproductive biology of a highly endemic species: Cipocereus laniflorus N.P. Taylor & Zappi (Cactaceae) - Rego,Juliana Ordones (2012)
Cipocereus laniflorus N.P. Taylor & Zappi is an endemic species from the Serra do Caraça, State of Minas Gerais, Brazil. In order to propose conservation strategies for this species, its reproductive strategies were investigated, including reproductive phenology, floral biology, floral visitors and breeding system. The flowering and fruiting period extends from May to October. Few flowers per plant open each night, producing up to 0.4 ml nectar, but 30% of them are nectarless. Probably pollen is also offered as a resource. Fruiting efficiency of C. laniflorus (47%) is close to that found in other Cactaceae species. Pollen of this species was detected in Anoura geoffroy, Soricina glossophaga and Pygoderma bilabiatum bats. Amongst the characteristics related to bat-pollination syndrome found in C. laniflorus, the cream-white colouring of the internal part of the flower, the numerous stamens and the nocturnal anthesis of short duration can be highlighted. Flowers of C. laniflorus are also visited by Nitidulidae beetles, Trigona fulviventris bees and hummingbirds, however bats are the main pollinators of this species. Finally, as a self-sterile species, C. laniflorus needs a pollinator and is more susceptible to the risk of extinction if local disturbances affect its pollination system.